2022
DOI: 10.3389/fnsyn.2022.959875
|View full text |Cite
|
Sign up to set email alerts
|

Differential modulation of collybistin conformational dynamics by the closely related GTPases Cdc42 and TC10

Abstract: Interneuronal synaptic transmission relies on the proper spatial organization of presynaptic neurotransmitter release and its reception on the postsynaptic side by cognate neurotransmitter receptors. Neurotransmitter receptors are incorporated into and arranged within the plasma membrane with the assistance of scaffolding and adaptor proteins. At inhibitory GABAergic postsynapses, collybistin, a neuronal adaptor protein, recruits the scaffolding protein gephyrin and interacts with various neuronal factors incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Previous studies demonstrated that activation of CB upon interacting with NL2 icd or TC10 leads to an open structure of CB, which allows CB to interact with phosphoinositides located in the postsynaptic membrane ( 29 , 33 , 34 , 55 ). The two-state Gaussian distributed distance fit of the CB F1 DA sensor showed an increase in the population of the low-FRET state upon interaction with NL2 icd , indicating NL2 icd -mediated CB opening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated that activation of CB upon interacting with NL2 icd or TC10 leads to an open structure of CB, which allows CB to interact with phosphoinositides located in the postsynaptic membrane ( 29 , 33 , 34 , 55 ). The two-state Gaussian distributed distance fit of the CB F1 DA sensor showed an increase in the population of the low-FRET state upon interaction with NL2 icd , indicating NL2 icd -mediated CB opening.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the SH3 domain lacking CB2 splice variant (CB2-SH3 − ) constitutively regenerates the GTP-bound state of Cdc42 ( 30 , 31 , 32 ). However, a recent study demonstrated that only TC10, another Dbl family GEF that is closely related to Cdc42 but not Cdc42, can effectively mediate the conformational activation of full-length CB ( 33 ). Interestingly, earlier biochemical and cellular studies ( 29 , 34 ) indicated that CB interaction with the cytosolic region of NL2 led to a similar activation of CB ( Fig.…”
Section: Introductionmentioning
confidence: 99%